Оцінка токсичноγo впливу питної води з різних джерел водопостачання на показники імунної системи щурів Bістар = Assessment of toxic effects of drinking water from various sources on indicators rats Vistar immune system. - Vergolyas, M. R.; Trakhtenberg, I. M.; Dmytrukha, N. M. (Journal of Education, Health and Sport, 2016)
Vergolyas M. R., Trakhtenberg I. M.,. Dmytrukha N. M. Оцінка токсичноγo впливу питної води з різних джерел водопостачання на показники імунної системи щурів Bістар = Assessment of toxic effects of drinking water from various sources on indicators rats Vistar immune system. Journal of Education, Health and Sport. 2016;6(9):855-866. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.161646 http://ojs.ukw.edu.pl/index.php/johs/article/view/3940 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. УДК 574.64:57.083.37 Оцінка токсичноΓO впливу питної води з рІзних джерел водопостачання на показники імунної системи ЩУРІВ ВІСТАР М. Р. Верголяс1, І. М. Трахтенберг2, Н. М. Дмитруха2 1Інститут колоїдної хімії та хімії води НАН України ім. А.В. Думанського, м Київ 2ДУ «Інститут медицини праці НАМН України, м. Київ. Реферат Досліджено реакцію імунної системи щурів на вплив питної води з водогону, бювету та фасовану воду. Відбір проб води для дослідження здійснювали у відповідності з методичними рекомендаціям ДСТУ ISO 5667-2:2003, також в усіх зразках води вимірювали вмісту макро- і мікроелементів за допомогою методу атомно-емісійної спектроскопії з індуктивно зв’язаною плазмою (Optima 2100 DV фірми Perkin Elmer, США). Контрольну воду підготовили в лабораторних умовах згідно з рекомендаціями ДСТУ 4174: 2003, яка не перевищувала нормативні показники - гранично допустиму концентрацію (ГДК) згідно з ДсанПін 2.2.4-171-10. Під час досліджень визначали відносну масу імунних органів – тимуса і селезінки контрольних та дослідних щурів. У всіх групах тварин визначали фагоцитарну активність нейтрофілів периферичної крові до полістиролового латексу, яка включала: фагоцитарний індекс – кількість фагоцитуючих нейтрофілів, та фагоцитарне число – середнє число часточок латексу, поглинутих одним нейтрофілом. У сироватці крові щурів визначали рівень циркулюючих імунних комплексів в реакції преципітації з поліетиленгліколем М=6000 (високомолекулярних – з 3,5% та низькомолекулярних – з 7,0 %). Всі дослідження на щурах проводились відповідно до конвенції Ради Європи щодо захисту хребетних тварин, яких використовують у наукових цілях. Аналіз отриманих даних показав, що після двох місяців вживання питної води з різних джерел водопостачання відносна маса селезінки достовірно знизилась в групі тварин, що пили воду з водогону (на 24,0%) і в 4-й групі, яким давали фасовану воду (на 26,0%). Це може вказувати на дистрофічні зміни в селезінці, які формуються за несприятливого впливу цих типів води. вживання води з водогону і бювету викликало несприятливий вплив на клітинні механізми неспецифічної природної резистентності, а саме, пригнічувало фагоцитарну активність нейтрофілів крові та резервні можливості фагоцитів, що в свою чергу може відобразитись на зниженні резистентності організму до інфекцій. В Україні та багатьох країн світу реалізації фасованої води збільшуються з кожним роком. Погіршення їх якості пов’язані зі змінами хімічного складу, мікробіологічними забрудненням, тривалістю і умовами зберігання, а також особливостями технологій водопідготовки. Для контролю якості питної води використовують фізико-хімічні методи визначення органолептичних, токсикологічних, фізіологічних показників та мікробіологічний аналіз. При цьому основними критеріями є значення концентрацій домішок, які визначені стандартами, та повноцінність складу води за макро- та мікроелементами. Вплив води на споживача може варіювати залежно, як від комбінації самих домішок, так і від їх концентрацій, навіть за умов відповідності встановленим нормам. Фізико-хімічні методи аналізу складу води не дають можливості вичерпно оцінювати якість води і прогнозувати комплексний вплив присутніх речовин у воді на біологічні об’єкти. На сучасному етапі все популярнішими стають методи біотестування, завдяки якій по реакції живої системи можна констатувати безпосереднє токсичний вплив питної води на організм. Ключові слова: біотестування, токсичність, якість води, гематологічні показники ASSESSMENT OF TOXIC EFFECTS OF DRINKING WATER FROM VARIOUS SOURCES ON INDICATORS RATS VISTAR IMMUNE SYSTEM M. R. Vergolyas1, I. M. Trakhtenberg2, N. M. Dmytrukha2 1Institute of colloid chemistry and water chemistry named A. V. Dumansky NAS Ukraine, 2State Institution Institute of Occupational Medicine of Medical Sciences of Ukraine, Kyiv. Abstract Researched the reaction of the immune system of rats on the impact of drinking water from water supply, pump room and packaged water. Sampling of water for research carried out in compliance with methodological recommendations of DSTU 5667-2: 2003, as in all samples measured water content of macro- and micronutrients by the method of atomic emission spectroscopy with inductively coupled plasma (Optima 2100 DV firm Perkin Elmer, USA). Control water have prepared in the laboratory as recommended by DSTU 4174: 2003, which was less than standard rates - the maximum permissible concentration (MPC) under STATE STANDARDS 2.2.4-171-10. During the research determined the relative weight of immune organs - the thymus and spleen of control and experimental rats. All groups of animals determined the phagocytic activity of peripheral blood neutrophils to polystyrene latex, which included: phagocytic index - the number of neutrophil phagocytic and phagocytic number - the average number of latex particles absorbed by one neutrophils. In rat serum determined level of circulating immune complexes in the reaction of polyethylene glycol precipitation N = 6000 (of high - from 3.5% and low - from 7.0%). All researches on rats conducted in accordance with the Council of Europe Convention for the protection of vertebrate animals used for scientific purposes. Analysis of the data has shown that after two months of use drinking water from various water sources relative spleen weight was significantly reduced in the group of animals that drank water from the water supply (24.0%) and the 4th group who were given packaged water (at 26.0%). This may indicate degenerative changes in the spleen, which are formed by the adverse effects of these types of water, drinking water from the water supply and pump room caused adverse effects on the cellular mechanisms of nonspecific natural resistance, namely depressed phagocytic activity of neutrophils and spare capacity of phagocytes, which in turn all could appear decrease in resistance to infection. In Ukraine and many countries realization of packaged water increases every year. The deterioration of the quality associated with changes in the chemical composition, microbiological contamination, duration and conditions of storage and features water treatment technologies. For control quality of drinking water using physical and chemical methods for determining the organoleptic, toxicological, physiological parameters and microbiological analysis. However, the main criteria are the concentrations of impurities that defined by standards, and usefulness of water for macro- and micronutrients. The impact of water on the consumer can vary depending on how the combination of most contaminants, and their concentrations, even in compliance with the standards. Physico-chemical methods of analysis of water make it impossible to comprehensively assess water quality and predicting complex effect substances present in the water on biological objects. Nowadays the more and more popular methods are becoming biological testing, through which the reaction of the living system may state a direct toxic effect of drinking water on the body. Key words: bioassay, toxicity, water quality, hematological parameters.